2004
DOI: 10.1021/bi0482304
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition in a Trans Excision-Splicing Ribozyme:  Non-Watson−Crick Base Pairs at the 5‘ Splice Site and ωG at the 3‘ Splice Site Can Play a Role in Determining the Binding Register of Reaction Substrates

Abstract: Trans excision-splicing (TES) ribozymes, derived from a Pneumocystis carinii group I intron, can catalyze the excision of targeted sequences from within RNAs. In this report, the sequence requirements of the splice sites are analyzed. These conserved sequences include a u-G wobble pair at the 5' splice site and a guanosine in the omega position at the 3' splice site (in the substrate). We report that 7 out of 16 base pair combinations at the 5' splice site produce appreciable TES product. This promiscuity is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
(105 reference statements)
0
10
0
Order By: Relevance
“…First, the initial ribozyme constructs lacked the nucleotides required to form the P10 helix (RE3), and so an RE3 region (native to the ribozyme) was added. As seen for the Pneumocystis ribozyme, P10 helix formation has been shown to aid in binding the 3′-exon region of TES substrates (9,10). Second, the 3′-end of each ribozyme sequence was modified to include the addition of a terminal guanosine, (which is found naturally) as it is required as the intramolecular nucleophile in the substrate-cleavage reaction (4).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…First, the initial ribozyme constructs lacked the nucleotides required to form the P10 helix (RE3), and so an RE3 region (native to the ribozyme) was added. As seen for the Pneumocystis ribozyme, P10 helix formation has been shown to aid in binding the 3′-exon region of TES substrates (9,10). Second, the 3′-end of each ribozyme sequence was modified to include the addition of a terminal guanosine, (which is found naturally) as it is required as the intramolecular nucleophile in the substrate-cleavage reaction (4).…”
Section: Resultsmentioning
confidence: 93%
“…This was done because the formation of the P10 helix interaction is important for the second reaction step of the TES reaction (9,10). Note that the RE3 sequence added was native to each respective intron.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the large number of splicing ribozymes determined by alignment, only several have ever been experimentally characterized and may not function as a self-splicing ribozyme in a bacterial host. Other ribozymes that have been studied include the ribozymes from Azoarcus (9,10), Pneumocystis (11,12), Didymium iridis (DiGIR2) (13,14), and Fuligo (Fse.L569 and Fse.L1898) (13). We tested two uncharacterized sequences found in the alignment for their ability to function as self-splicing ribozymes, but neither ribozyme showed cis -splicing activity (Supplementary Data).…”
Section: Discussionmentioning
confidence: 99%
“…Other considerations for ribozyme targeting include reconstituting au-G wobble pair at the 5 0 splice site and aguanosine at the 3 0 splice site as the last (or only) base of the sequence targeted for excision (Baum et al 2005). Also note that previous work with this ribozyme demonstrated that segments larger than a single nucleotide can be excised in vitro (Bell et al 2002), so we anticipate that larger regions could be excised in vivo.…”
Section: Discussionmentioning
confidence: 99%